High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

Comparative genome analysis of the Sphaerotilus-Leptothrix group supports the unification of the genera Sphaerotilus and Leptothrix into a single emended genus Sphaerotilus - Dmitry D. Smolyakov; Alexey V. Beletsky; Tatyana S. Rudenko; Maria V. Gureeva; Nikolai V. Ravin; Margarita Y. Grabovich (Systematic and Applied Microbiology, 2025)

NMR metabolomics in genetically engineered mouse models - Kamil N. Aysin; Alexander Yu. Rudenko; Sofia S. Mariasina; Vladimir I. Polshakov (Biophysical Reviews, 2025)

Modeling of Frequency Dependence of Selectivity and Sensitivity of Mammalian Otolith Membranes during Electrical Stimulation of the Vestibular Nerves - V. V. Udut; V. P. Demkin; S. V. Melnichuk; T. V. Rudenko; M. V. Svetlik; M. D. Akinina; O. V. Demkin; L. V. Smaglii; V. M. Alifirova; O. V. Grebenuk (Bulletin of Experimental Biology and Medicine, 2025)

Serological and molecular typing of Tenacibaculum maritimum from New Zealand farmed salmon, Oncorhynchus tshawytscha - Karthiga Kumanan; Lizenn Delisle; Connie Angelucci; Ryan B.J. Hunter; Oleksandra Rudenko; Jeremy Carson; Richard N. Morrison; Andrew C. Barnes; Kate S. Hutson (Aquaculture, 2024)

Molecular mimicry of the receptor-binding domain of the SARS-CoV-2 spike protein: from the interaction of spike-specific antibodies with transferrin and lactoferrin to the antiviral effects of human recombinant lactoferrin - A. V. Sokolov; I. N. Isakova-Sivak; D. A. Mezhenskaya; V. A. Kostevich; N. P. Gorbunov; A. Yu. Elizarova; V. A. Matyushenko; Yu. M. Berson; N. A. Grudinina; N. N. Kolmakov; Y. A. Zabrodskaya; A. S. Komlev; et al. (BioMetals, 2023)

Modeling of Chronic Lung Inflammation in Rats by Repeated Intratracheal Administration of LPS - V. A. Palikov; Yu. A. Palikova; P. A. Rudenko; V. A. Kazakov; N. A. Borozdina; I. N. Kravchenko; I. A. Pakhomova; E. N. Kazakova; G. A. Slashcheva; S. G. Semushina; O. N. Khokhlova; I. A. Dyachenko (Bulletin of Experimental Biology and Medicine, 2022)

Reclassification of Sphaerotilus natans subsp. sulfidivorans Gridneva et al. 2011 as Sphaerotilus sulfidivorans sp. nov. and comparative genome analysis of the genus Sphaerotilus - Margarita Y. Grabovich; Dmitry D. Smolyakov; Alexey V. Beletsky; Andrey V. Mardanov; Maria V. Gureeva; Nikita D. Markov; Tatyana S. Rudenko; Nikolai V. Ravin (Archives of Microbiology, 2021)

Effect of Standard and High-Fat Diets during Modeling of Streptozotocin-Induced Diabetes in Rats on the Development of Complications - E. R. Shaykhutdinova; V. A. Palikov; Y. A. Palikova; N. A. Borozdina; I. N. Kravchenko; E. S. Sadovnikova; I. A. Pakhomova; P. A. Rudenko; V. A. Kazakov; T. Y. Zharmukhamedova; O. N. Khokhlova; I. A. Dyachenko (Bulletin of Experimental Biology and Medicine, 2021)

Spectral Regularities of Viscoelastic Parameters of Whole Blood Exposed to Periodic Shear Stress - V. P. Demkin; S. V. Mel’nichuk; A. V. Gavar; O. V. Demkin; T. V. Rudenko; E. V. Udut; I. I. Tyutrin; V. V. Udut (Bulletin of Experimental Biology and Medicine, 2020)

Analysis of Viscoelastic Parameters of Fluids by Low-Frequency Piezoelastography - V. P. Demkin; S. V. Mel’nichuk; T. V. Rudenko; I. I. Tyutrin; V. V. Udut (Bulletin of Experimental Biology and Medicine, 2020)

Amino Acid Substitutions N123D and N149D in Hemagglutinin Molecule Enhance Immunigenicity of Live Attenuated Influenza H7N9 Vaccine Strain in Experiment - E. A. Stepanova; T. S. Kotomina; V. A. Matyushenko; T. A. Smolonogina; V. S. Shapovalova; L. G. Rudenko; I. N. Isakova-Sivak (Bulletin of Experimental Biology and Medicine, 2019)

Modeling of 3D Structure of Chimeric Constructs Based on Hemagglutinin of Influenza Virus and Immunogenic Epitopes of Streptococcus Agalactiae - E. A. Fedorova; T. A. Smolonogina; I. N. Isakova-Sivak; D. A. Koren’kov; T. S. Kotomina; G. F. Leont’eva; A. N. Suvorov; L. G. Rudenko (Bulletin of Experimental Biology and Medicine, 2018)

Variability of the Expression of Reference Genes in Samples of Human Olfactory Epithelium - S. P. Kovalenko; N. S. Rudenko; A. S. Avdeeva; K. V. Danilenko; L. I. Aftanas (Bulletin of Experimental Biology and Medicine, 2018)

Mid- and late-Holocene vegetation history, climate and human impact in the forest-steppe ecotone of European Russia: new data and a regional synthesis - Elena Y. Novenko; Andrey N. Tsyganov; Olga V. Rudenko; Elena V. Volkova; Inna S. Zuyganova; Kirill V. Babeshko; Alexander V. Olchev; Nikolai I. Losbenev; Richard J. Payne; Yuri A. Mazei (Biodiversity and Conservation, 2016)

C-Type Natriuretic Peptide: What, Where and Why? - I. M. Korostyshevskaya; V. F. Maksimov; N. S. Rudenko (Neuroscience and Behavioral Physiology, 2016)

Analysis of Immune Epitopes of Respiratory Syncytial Virus for Designing of Vectored Vaccines Based on Influenza Virus Platform - I. N. Isakova-Sivak; D. A. Korenkov; E. A. Fedorova; T. S. Tretiak; V. A. Matyushenko; T. A. Smolonogina; L. G. Rudenko (Bulletin of Experimental Biology and Medicine, 2016)

Improved sea level record over the satellite altimetry era (1993–2010) from the Climate Change Initiative project - M. Ablain; A. Cazenave; G. Larnicol; M. Balmaseda; P. Cipollini; Y. Faugère; M. J. Fernandes; O. Henry; J. A. Johannessen; P. Knudsen; O. Andersen; J. Legeais; et al. (Ocean Science, 2015)
Sea level is one of the 50 Essential Climate Variables (ECVs) listed by the Global Climate Observing System (GCOS) in climate change monitoring. In the past two decades, sea level has been routinely measured from space using satellite altimetry techniques. In order to address a number of important scientific questions such as "Is sea level rise accelerating?", "Can we close the sea level budget?", "What are the causes of the regional and interannual variability?", "Can we already detect the anthropogenic forcing signature and separate it from the internal/natural climate variability?", and "What are the coastal impacts of sea level rise?", the accuracy of altimetry-based sea level records at global and regional scales needs to be significantly improved. For example, the global mean and regional sea level trend uncertainty should become better than 0.3 and 0.5 mm year−1, respectively (currently 0.6 and 1–2 mm year−1). Similarly, interannual global mean sea level variations (currently uncertain to 2–3 mm) need to be monitored with better accuracy. In this paper, we present various data improvements achieved within the European Space Agency (ESA) Climate Change Initiative (ESA CCI) project on "Sea Level" during its first phase (2010–2013), using multi-mission satellite altimetry data over the 1993–2010 time span. In a first step, using a new processing system with dedicated algorithms and adapted data processing strategies, an improved set of sea level products has been produced. The main improvements include: reduction of orbit errors and wet/dry atmospheric correction errors, reduction of instrumental drifts and bias, intercalibration biases, intercalibration between missions and combination of the different sea level data sets, and an improvement of the reference mean sea surface. We also present preliminary independent validations of the SL_cci products, based on tide gauges comparison and a sea level budget closure approach, as well as comparisons with ocean reanalyses and climate model outputs.

Inhibition of Secretory Activity of Atrial Myocytes in Hypertensive Rats after Losartan Treatment - V. F. Maksimov; I. M. Korostyshevskaya; A. L. Markel’; G. S. Yakobson; N. S. Rudenko (Bulletin of Experimental Biology and Medicine, 2015)

GGOS-D: homogeneous reprocessing and rigorous combination of space geodetic observations - M. Rothacher; D. Angermann; T. Artz; W. Bosch; H. Drewes; M. Gerstl; R. Kelm; D. König; R. König; B. Meisel; H. Müller; A. Nothnagel; et al. (Journal of Geodesy, 2011)

Energy conservation and second-order statistics in stably stratified turbulent boundary layers - Victor S. L’vov; Itamar Procaccia; Oleksii Rudenko (Environmental Fluid Mechanics, 2009)

Electron Microscopic Study of DNA Packing in ϕkz Bacteriophage (Pseudomonas Aeruginosa) Irradiated with Laser in the Presence of a Dye - A. A. Manykin; N. N. Gabyshev; N. B. Matsko; A. G. Leonov; A. A. Rudenko; D. I. Chekhov; S. M. Klimenko (Bulletin of Experimental Biology and Medicine, 2001)